PENGARUH ROA, NPM, EPS, DAN PBV TERHADAP HARGA SAHAM SEKTOR ENERGI YANG TERDAFTAR DI BEI - NAUFAL DZAKWAN; ERVIVA FARIANTIN; ELVINA SETIAWATI (GANEC SWARA, 2023)
This study aims to determine the effect of ROA, NPM, EPS and PBV on stock prices of energy sector companies listed on the Indonesia Stock Exchange. The sampling method used is purposive sampling with certain criteria by using multiple linear regression test data analysis techniques. The multiple linear regression equation is Y = 275.846 + 3.109 ROA - 0.677 NPM + 3.303 EPS + 426,637 PBV. The results showed that ROA (X1) had no effect on stock prices with a t value of 0.478 < 2.042, NPM (X2) had a negative and insignificant effect on stock prices and a t-value of -2.744 > 2.042, EPS (X3) had a positive and significant effect on stock prices. with a t-value of 4.015 > 2.042, and PBV (X4) has a positive and significant effect on stock prices with a t-value of 6.178 > 2.042